Comparison of clinical, clinicopathologic, and histologic variables in dogs with chronic inflammatory enteropathy and low or normal serum 25‐hydroxycholecalciferol concentrations. (9th September 2019) - Wennogle, Sara A.; Priestnall, Simon L.; Suárez‐Bonnet, Alejandro; Webb, Craig B.
Abstract: Background: The cause of low serum vitamin D concentrations in dogs with chronic inflammatory enteropathy (CIE) is not well understood. Objective: Improve understanding of pathogenesis of low serum vitamin D concentrations in dogs with CIE by comparing several clinical, clinicopathologic, and histologic variables between CIE dogs with low and normal serum 25‐hydroxyvitamin D concentrations (25[OH]D). Animals: Fifteen dogs with CIE and low serum 25[OH]D concentrations; 15 dogs with CIE and normal serum 25(OH)D concentrations. Methods: Prospective cohort study. Clinical and clinicopathologic variables were compared between groups. Correlations between serum 25(OH)D concentration and histopathologic variables were assessed. Results: Dogs with CIE and low serum 25(OH)D concentrations had higher canine chronic enteropathy clinical activity index scores ( P = .003), lower serum α‐tocopherol ( P < .001), cholesterol ( P < .001), and albumin ( P < .001) concentrations and higher serum C‐reactive protein ( P = .004) concentrations compared to CIE dogs with normal serum 25(OH)D concentrations. Serum concentrations of vitamin D‐binding protein (VDBP) were not different between groups ( P = .91). Duodenal morphologic and inflammatory histopathological scores ( P = .002 and P = .004, respectively) and total histopathological scores in duodenum and combined duodenum and ileum negatively correlated with serum 25(OH)D concentration. Conclusions and Clinical Importance: The pathogenesis of low serum vitamin D concentrations in dogs with CIE is likely multifactorial. Fat malabsorption deserves further study in dogs with low serum vitamin D concentration and CIE. Loss of VDBP does not appear to be an important cause of low serum vitamin D concentration in dogs with CIE.